Aneurisma del tronco braquiocefálico con compresión de vía aérea - Gabriel Atanasio; Maria Ana Canelas (Sociedade Galega de Medicina Interna, 2021)
Brachiocephalic trunk (BCT) aneurysms are rare but very important since they pose a significant threat to life and limbs due to the risk of rupture, embolization, or compression of the adjacent structures. We now present a case of a BCT aneurysm with tracheal compression leading to difficult ventilator weaning.